Body height from tooth size: A novel study on stature estimation by odontometric parameters - Yesha Jani; Shilpa Parikh; Bhavin Dudhia; Parul Bhatia; Purv Patel; Roseline Patel (Wolters Kluwer Medknow Publications, 2018)
Introduction: Stature is the height of a person in the upright posture. Based upon the principle that the various long bones correlate positively with stature, stature correlation to skull and jaw dimensions has been frequently reported among various populations. Objective: The study was conducted to investigate the possibility of predicting the height of an individual using selected odontometric parameters as a forensic tool. Materials and Methods: The study sample consisted of 100 randomly selected subjects. Measurements of maxillary intercanine width (IC), maxillary interpremolar width (IP), and mesiodistal width of six permanent maxillary anterior teeth (CW) were made directly on the subject by means of a digital vernier caliper. Height (H) of patients was measured with anthropometer. Results: Significant correlation was observed between height and maxillary IC width (P < 0.05), whereas correlation between height and the combined width of six anterior teeth as well as IP width was found to be nonsignificant. Conclusion: The maxillary IC width can be used successfully to calculate the stature of an individual from fragmentary remains.